SPOP and CHD1 alterations in prostate cancer: Relationship with PTEN loss, tumor grade, perineural infiltration, and PSA recurrence. Issue 16 (17th September 2021) - Hernández‐Llodrà, Silvia; Segalés, Laura; Juanpere, Nuria; Marta Lorenzo, Tech; Salido, Marta; Nonell, Lara; David López, Tech; Rodríguez‐Vida, Alejo; Bellmunt, Joaquim; Fumadó, Lluís; Cecchini, Lluís; Lloreta‐Trull, Josep
Abstract: Background: In the non‐ ETS fusion of prostate cancer (PCa) pathway, SPOP mutations emerge as a distinct oncogenic driver subclass. Both SPOP downregulation and mutation can lead to SPOP target stabilization promoting dysregulation of key regulatory pathways. CHD1 gene is commonly deleted in PCa. CHD1 loss significantly co‐occurs with SPOP mutations, resulting in a PCa subclass with increased AR transcriptional activity and with a specific epigenetic pattern. Methods: In this study, SPOP alterations at mutational and protein levels and CHD1 copy number alterations have been analyzed and correlated with ERG and PTEN protein expression and with the clinical pathological features of the patients. Results: SPOP protein loss has been detected in 42.9% of the cases, and it has been strongly associated with PTEN protein loss ( p < .001). CHD1 gene loss has been detected in 24.5% and SPOP mutations in 5.9% of the cases. Loss of CHD1 has been strongly associated with SPOP mutations ( p = .003) and has shown a trend to be associated with ERG wt cancers ( p = .08). The loss of SPOP protein ( p = .01) and the combination of PTEN and SPOP protein loss ( p = .002) were both statistically more common in grade group 5 cancers, with a prevalence of 60% and 37.5%, respectively. Furthermore, SPOP loss/PTEN loss and SPOP wt /PTEN loss phenotypes were strongly associated with extraprostatic perineural infiltration ( p = .007). Strong CHD1 loss was associated with a shorter time to PSA recurrence in the univariate ( p = .04), and showed a trend to be associated with the PSA recurrence risk in the multivariate analysis ( p = .058). Conclusions: The results of the present study suggest that the loss of SPOP protein expression, either alone or in combination with loss of PTEN and, on the other hand, a marked loss of the CHD1 gene are very promising prognostic biomarkers in PCa.